The preclinical evaluation of immunocontraceptive vaccines based on canine zona pellucida 3 (cZP3) in a mouse model - Ying Wang; Yijie Li; Beibei Zhang; Fuchun Zhang (BMC, 2018)
Abstract Background Stray dogs are the reservoirs and carriers of rabies and are definitive hosts of echinococcosis. To control the overpopulation of stray dogs, zona pellucida 3 (ZP3), a primary receptor for sperm, is a potential antigen for developing contraceptive vaccines. To enhance the immune responses and contraceptive effects of canine ZP3 (cZP3), dog gonadotropin-releasing hormone (GnRH) and a T cell epitope of chicken ovalbumin (OVA) were selected to construct two fusion proteins with cZP3, ovalbumin-GnRH-ZP3 (OGZ) and ovalbumin-ZP3 (OZ), and their contraceptive effects were evaluated in mice. Methods The synthesized DNA sequences of OGZ and OZ were cloned into plasmid pET-28a respectively. The fusion proteins OGZ and OZ were identified by SDS-PAGE and Western blot. Mice were immunized with OGZ, OZ and cZP3, and the infertility rates were monitored. Mice immunized with mouse ZP3 (mZP3) or adjuvant alone were used as positive control and negative control, respectively. cZP3- and GnRH-specific antibodies (Abs) were detected by ELISA. The bindings of the Abs to oocytes were detected by indirect immunofluorescence assay. The paraffin sections of mice ovaries were observed under microscope for analyzing pathological characteristics. Results SDS-PAGE and Western blot analyses showed that the two fusion proteins OGZ and OZ were correctly expressed. ELISA results showed that OGZ vaccine induced both cZP3- and GnRH-specific Abs, and OZ vaccine induced cZP3-specific Ab, which lasted for up to 168 days. The levels of follicle stimulating hormone (FSH) and estradiol (E2) in sera were significantly decreased in OGZ immunized mice. Indirect immunofluorescence results showed that Abs induced by cZP3 and mZP3 could bind to the mouse ZP and dog ZP each other. Compared with the adjuvant group, all vaccine immunized groups significantly decreased the fertility rate and mean litter size. Interestingly, the fertility rate in OGZ-immunized group is the lowest, and only 1 mouse out of 10 mice is fertile. Histological analysis of murine ovarian sections indicated that most of the infertile mice in the immunized groups lacked mature follicles as well as accompanied by inflammatory infiltration. Meanwhile, immunization with OGZ decreased the number of corpora lutea in the infertile mice. Conclusions The fusion protein OGZ resulted in the lowest fertility rate and the least mean litter size in the immunized mice. OGZ might be a promising antigen for developing a new contraceptive vaccine for stray dog controlling.